Use of GPS for a Berthing Guidance System - Ueno, Mami (The International Hydrographic Review, 2018)
The research was conducted in view of automatic berthing of a large merchant ship. This paper discusses the general concept of an automatic berthing system. A GPS-based system, which provides the necessary information on position, velocity, attitude (roll, pitch, and heading), angular velocity and time, will be a principal sensor in a berthing system. The tests were conducted on board a hydrographic sounding ship to obtain the information from a GPS-based system. The data was processed using the software where the algorithms developed in this research are implemented. This paper also discusses various aspects concerning the real-time GPS-based system in relation to an automatic berthing system, such as integration of sensors, port infrastructure, training of crews.